High-performance sodium ion battery positive electrode material and preparation method and application thereof
By adopting the method of co-doping of Cu, Li and Ti in the positive electrode material of sodium ion battery, the problem of irreversible phase change of nickel-manganese base layered oxides at high voltage is solved, which significantly improves the cyclic stability and capacity retention of the material, and reduces the cost.
Patent Information
- Application Number
- CN202411648551.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing sodium ion battery positive electrode materials have irreversible phase change at high voltages, resulting in rapid deterioration of capacity and degradation of cycling performance, limiting the practical application of the material.
The direct solid phase calcination method is adopted and the method of co-doping Cu, Li and Ti is used to inhibit the adverse phase change of nickel-manganese base layer oxide in the electrochemical reaction and the phase structure transformation during the charge and discharge process, and improve the electrochemical cycle stability.
Through the coordinated doping of Cu, Li and Ti elements, the cycle stability of sodium ion batteries is significantly improved. After cycling for 100 cycles at 1C current density, the capacity retention rate reaches up to 98.55%, and the cost of the material is reduced.
Smart Images

Figure CN119143200B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion battery positive electrode materials, and specifically relates to a high-performance sodium ion battery positive electrode material and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries (SIBs) have attracted increasing attention for large-scale electrochemical energy storage devices due to their suitable electrochemical potential, cheap and naturally abundant sodium reserves. To date, many researchers have extensively studied various sodium-ion battery cathode materials, such as transition metal layered oxides, sulfates, and polyanionic compounds that can serve as SIB cathodes. Among the numerous cathode materials, transition metal layered oxides have received keen attention due to their high specific capacity and tunable electrochemical properties. Among them, the representative nickel-manganese-based layered oxide material has high operating voltage and multivalent nickel redox reaction, showing high capacity characteristics. However, its irreversible phase transition at high voltage leads to rapid capacity deterioration and decreased cycle performance, limiting the practical application of the material.
[0003] For example, the patent with publication number CN 116936761 A discloses a positive electrode composite material, the general formula of which is Na δ Li a (Ni x M y Mn z ) b Ti c O 2 , M is at least one of the transition metal elements other than Ni, Mn and Ti. The cathode composite material has a discharge capacity of 165 mAh / g at a rate of 0.2 C, but its capacity retention rate after 100 cycles at 1 C is only 80%, and the cycle stability needs to be further improved. Therefore, the development of sodium ion battery cathode materials with high cycle stability is of great practical significance for promoting the development of sodium ion battery technology. Summary of the invention
[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a method for preparing a high-performance sodium ion battery positive electrode material, which adopts a direct solid phase calcination method and synergistic doping of Cu, Li, and Ti to inhibit the adverse phase change of nickel-manganese-based layered oxides in electrochemical reactions, the phase structure transformation and volume change during the charge and discharge process, and improve the electrochemical cycle stability.
[0005] Another object of the present invention is to provide a high-performance sodium ion battery positive electrode material obtained by the above-mentioned preparation method, wherein the high-performance sodium ion battery positive electrode material is a nickel-manganese-based layered oxide co-doped with Cu, Li, and Ti, and has a layered structure of O3 phase.
[0006] Another object of the present invention is to provide an application of the above-mentioned high-performance sodium ion battery positive electrode material in a sodium ion battery.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] A method for preparing a high-performance sodium ion battery positive electrode material comprises the following steps:
[0009] Step 1, mixing a sodium source, a nickel source, a manganese source, a copper source, a lithium source and a titanium source until uniform, to obtain a precursor powder, wherein the ratio of sodium in the sodium source, nickel in the nickel source, manganese in the manganese source, copper in the copper source, lithium in the lithium source and titanium in the titanium source is 1.05: (0.5-xyz): 0.5: x: 1.05y: z, wherein x=0.15, y=0.05, z=y, and the capacity retention rate of the sodium ion battery prepared by the high-performance sodium ion battery positive electrode material at a current density of 1C is up to 98.55%;
[0010] In step 1, the sodium source is one or a mixture of sodium acetate, sodium carbonate, sodium bicarbonate, sodium nitrate and sodium hydroxide.
[0011] In step 1, the nickel source is one or a mixture of nickel oxide, nickel chloride, nickel hydroxide, nickel acetylacetonate, nickel ethoxide and nickel nitrate.
[0012] In step 1, the manganese source is one or a mixture of manganese oxide, manganese chloride, manganese hydroxide, manganese acetylacetonate, manganese ethanolate and manganese nitrate.
[0013] In step 1, the copper source is one or a mixture of copper oxide, copper chloride, copper hydroxide, copper acetylacetonate, copper ethoxide and copper nitrate.
[0014] In step 1, the lithium source is one or a mixture of lithium oxide, lithium chloride, lithium hydroxide, lithium carbonate, lithium ethanolate and lithium nitrate.
[0015] In step 1, the titanium source is one or a mixture of titanium oxide, titanium chloride and titanium hydroxide.
[0016] In step 1, the method of mixing the sodium source, nickel source, manganese source, copper source, lithium source and titanium source until they are uniform is one of dry ball milling, wet ball milling, spray drying and sol-gel method.
[0017] Step 2: sintering the precursor powder at 850-950° C. for 12-14 h to obtain a high-performance sodium ion battery positive electrode material.
[0018] In step 2, the temperature is raised to 850-950°C at a rate of 4-6°C / min.
[0019] The high-performance sodium ion battery positive electrode material obtained by the above preparation method.
[0020] The application of the above-mentioned high-performance sodium ion battery positive electrode material in sodium ion batteries to improve the cycle stability.
[0021] In the above technical scheme, the sodium ion battery prepared from high-performance sodium ion battery positive electrode material was cycled 100 times at a current density of 1C, and the capacity retention rate was as high as 98.55%.
[0022] In the above technical solution, the sodium ion battery includes a liquid sodium ion battery and a solid sodium ion battery.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The high-performance sodium ion battery cathode material of the present invention is obtained by co-substituting Ni with Cu, Li and Ti elements, and stabilizing the lattice through the synergistic effect of doping the three elements, thereby optimizing the cycle stability of the sodium ion battery.
[0025] 2. The sodium ion battery of the present invention has good cycle stability. After 100 cycles at a current density of 1C, the capacity retention rate is as high as 98.55%.
[0026] 3. The present invention uses low-cost Cu, Li and Ti to replace Ni element, which is beneficial to further reduce the cost of nickel-manganese-based layered oxide positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 XRD diagram of the high performance sodium ion battery positive electrode material prepared in Examples 1 to 3;
[0028] Figure 2 This is a SEM image of the high-performance sodium ion battery positive electrode material prepared in Example 1;
[0029] Figure 3 This is a SEM image of the high-performance sodium ion battery positive electrode material prepared in Example 2;
[0030] Figure 4 This is a SEM image of the high-performance sodium ion battery positive electrode material prepared in Example 3;
[0031] Figure 5 The charge and discharge curves of the sodium ion batteries prepared in Examples 4 to 6 are as follows;
[0032] Figure 6The cycle performance diagram of the sodium ion battery prepared in Examples 4 to 6;
[0033] Figure 7 XRD diagram of the sodium ion battery positive electrode material prepared in Comparative Examples 1 to 3;
[0034] Figure 8 This is a SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 1;
[0035] Fig. 9 This is a SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 2;
[0036] Fig.10 This is a SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 3;
[0037] Fig.11 The charge and discharge curves of the sodium ion batteries prepared in Comparative Examples 4 to 6 are shown;
[0038] Fig.12 This is a cycle performance diagram of the sodium ion batteries prepared in Comparative Examples 4 to 6. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0040] The sources of the raw materials involved in the following examples are shown in Table 1:
[0041] Table 1
[0042]
[0043] The various performance indicators in the following examples are strictly measured using precise instruments or standard test methods:
[0044] The XRD patterns were measured by an X-ray diffractometer (ARL EQUINOX 3000, Thermo Fisher Scientific) at 40 kV and 40 mA in the 2θ range of 10 to 80°.
[0045] The microstructure was characterized by using a Quanta FEG 250 field emission scanning electron microscope and a Verios 460L ultra-high resolution field emission scanning electron microscope from FEI Company of the United States.
[0046] On the LAND system (LAND CT2001A, China), at 2.0 - 4.2 V (vs. Na / Na + ) potential window for constant current charge and discharge measurements and cycle performance tests.
[0047] Embodiment 1~3
[0048] A method for preparing a high-performance sodium ion battery positive electrode material comprises the following steps:
[0049] Step 1, a sodium source, a nickel source, a manganese source, a copper source, a lithium source and a titanium source are mixed in a ball mill, wet-milled at a speed of 1800 rpm for 2 h until uniform, and dried in a vacuum oven at 80 ° C for 12 h to obtain a precursor powder, wherein the ratio of sodium in the sodium source, nickel in the nickel source, manganese in the manganese source, copper in the copper source, lithium in the lithium source and titanium in the titanium source is X, and the value of X is shown in Table 2, the sodium source is sodium carbonate, the nickel source is nickel oxide (nickel oxide), the manganese source is manganese oxide (manganese trioxide), the copper source is copper oxide (copper oxide), the lithium source is lithium carbonate (lithium carbonate), the titanium source is titanium oxide (titanium dioxide), the ball-to-material ratio of wet ball milling is 5:1, and the ball milling medium is acetone (the amount of acetone added is more than the ball material);
[0050] Step 2: Place the precursor powder into an alumina crucible, transfer it into a muffle furnace, heat it to 900 °C at a rate of 5 °C / min, sinter it at 900 °C for 12 h, cool it to room temperature (20-25 °C) with the furnace, grind it into powder with a mortar, and obtain a high-performance sodium ion battery positive electrode material.
[0051] Table 2
[0052]
[0053] In Examples 1 to 3, the doping amounts of Cu, Li, and Ti are not high, and will not change the phase structure of the material and affect the specific capacity of the material. In this molecular structure, Mn and Ni are the main redox substances, Cu enhances air stability, and Li and Ti inhibit phase change.
[0054] Comparative Example 1
[0055] A sodium ion battery positive electrode material (NaNi 0.35 Mn 0.55 Cu 0.1 O 2 ), comprising the following steps:
[0056] Step 1, mixing a sodium source, a nickel source, a manganese source and a copper source in a ball mill, wet-milling at a rotation speed of 1800 rpm for 2 hours until uniform, and drying in a vacuum oven at 80 ° C for 12 hours to obtain a precursor powder, wherein the ratio of sodium in the sodium source, nickel in the nickel source, manganese in the manganese source and copper in the copper source is 1.05:0.35:0.55:0.1 in terms of the amount of substance, the sodium source is sodium carbonate, the nickel source is nickel oxide (nickel oxide), the manganese source is manganese oxide (manganese trioxide), the copper source is copper oxide (copper oxide), the ball-to-material ratio of wet ball milling is 5:1, and the ball milling medium is acetone (the amount of acetone added is more than the ball material);
[0057] Step 2: Place the precursor powder into an alumina crucible, transfer it to a muffle furnace, heat it to 900 °C at a rate of 5 °C / min, sinter it at 900 °C for 12 hours, cool it to room temperature (20-25 °C) with the furnace, grind it into powder with a mortar, and obtain a positive electrode material for a sodium ion battery.
[0058] Comparative Example 2
[0059] A sodium ion battery positive electrode material (NaNi 0.35 Mn 0.5 Cu 0.1 Ti 0.05 O 2 ), comprising the following steps:
[0060] Step 1, mixing a sodium source, a nickel source, a manganese source, a copper source and a titanium source in a ball mill, wet-milling at a speed of 1800 rpm for 2 hours until uniform, and drying in a vacuum oven at 80 ° C for 12 hours to obtain a precursor powder, wherein the ratio of sodium in the sodium source, nickel in the nickel source, manganese in the manganese source, copper in the copper source and titanium in the titanium source is 1.05:0.35:0.5:0.1:0.05 in terms of the amount of substance, the sodium source is sodium carbonate, the nickel source is nickel oxide (nickel oxide), the manganese source is manganese oxide (manganese trioxide), the copper source is copper oxide (copper oxide), the titanium source is titanium oxide (titanium dioxide), the ball-to-material ratio of wet ball milling is 5:1, and the ball milling medium is acetone (the amount of acetone added is more than the ball material);
[0061] Step 2: Place the precursor powder into an alumina crucible, transfer it into a muffle furnace, heat it to 900 °C at a rate of 5 °C / min, sinter it at 900 °C for 12 h, cool it to room temperature (20-25 °C) with the furnace, grind it into powder with a mortar, and obtain a positive electrode material for a sodium ion battery.
[0062] Comparative Example 3
[0063] A sodium ion battery positive electrode material (NaNi 0.3 Mn 0.55 Cu 0.1 Li 0.05 O 2 ), comprising the following steps:
[0064] Step 1, mixing a sodium source, a nickel source, a manganese source, a copper source and a lithium source in a ball mill, wet-milling at a speed of 1800 rpm for 2 hours until uniform, and drying in a vacuum oven at 80 ° C for 12 hours to obtain a precursor powder, wherein the ratio of sodium in the sodium source, nickel in the nickel source, manganese in the manganese source, copper in the copper source and lithium in the lithium source is 1.05:0.3:0.55:0.1:0.0525 in terms of the amount of substance, the sodium source is sodium carbonate, the nickel source is nickel oxide (nickel oxide), the manganese source is manganese oxide (manganese trioxide), the copper source is copper oxide (copper oxide), the lithium source is lithium carbonate (lithium carbonate), the ball-to-material ratio of wet ball milling is 5:1, and the ball milling medium is acetone (the amount of acetone added is greater than the ball material);
[0065] Step 2: Place the precursor powder into an alumina crucible, transfer it into a muffle furnace, heat it to 900 °C at a rate of 5 °C / min, and sinter it at 900 °C for 12 hours. After cooling it to room temperature of 20-25 °C, grind it into powder with a mortar to obtain a positive electrode material for a sodium ion battery.
[0066] Examples 4 to 6 and Comparative Examples 4 to 6
[0067] A method for preparing a sodium ion battery comprises: in a glove box, assembling a positive electrode shell, a positive electrode sheet, a diaphragm, a negative electrode sheet, a gasket, a spring sheet, and a negative electrode shell in order to obtain a sodium ion battery, wherein the electrolyte in the electrolyte solution is NaClO 4 The concentration of electrolyte in the electrolyte is 1 mol L -1 The solvent in the electrolyte is a mixture of propylene carbonate (PC) and fluoroethylene carbonate (FEC), and the ratio of propylene carbonate to fluoroethylene carbonate is 95:5 by volume. The negative electrode is a sodium sheet, and the separator is a porous glass fiber. The method for obtaining the positive electrode is: mixing the positive electrode material, the conductive agent (acetylene black) and the binder solution (the binder solution is a mixture of polyvinylidene fluoride (PVDF) and N-methylpyrrolidone, and the concentration of polyvinylidene fluoride in the binder solution is 20 mg mL -1, the ratio of the positive electrode material, the conductive agent and the polyvinylidene fluoride in the binder solution is 8:1:1 by mass), put it into an agate mortar and grind it for 30 min until it is uniform, and obtain a slurry. The slurry is evenly coated on the carbon-containing aluminum foil (the carbon-containing aluminum foil is single-sided carbon-coated (single-sided coating thickness is 1 μm)) as the current collector with a scraper, and dried in a vacuum oven at 80°C for 12 hours to fully volatilize N-methylpyrrolidone (NMP). When the vacuum oven temperature drops to room temperature, take it out, cut out a circular electrode sheet with a diameter of 12 mm with a sheet cutter, and then use a sheet press to keep the obtained circular electrode sheet at a pressure of 10 MPa for 30 seconds to obtain a positive electrode sheet (the positive electrode material loading on the circular electrode sheet with a diameter of 12 mm is 1-1.3 mg). The positive electrode material is one of the high-performance sodium ion battery positive electrode materials prepared in Examples 1 to 3 and the sodium ion battery positive electrode materials prepared in Comparative Examples 1 to 3 (as shown in Table 3).
[0068] Table 3
[0069]
[0070] The XRD patterns of the high performance sodium ion battery cathode materials prepared in Examples 1 to 3 are as follows: Figure 1 As shown, after XRD analysis, Figure 1 The diffraction peak intensity of the high-performance sodium ion battery positive electrode material prepared in Examples 1 to 3 is relatively high, indicating that it has good crystallinity and has characteristic peaks of the triclinic R3m space group, indicating that the element doping in Examples 1 to 3 forms a layered structure of the O3 phase.
[0071] The SEM image of the high performance sodium ion battery positive electrode material prepared in Example 1 is as follows Figure 2 As shown, the high-performance sodium ion battery cathode material prepared in Example 1 presents a plate-like structure with a smooth surface and uniform size; the SEM image of the high-performance sodium ion battery cathode material prepared in Example 2 is as shown Figure 3 As shown, the high-performance sodium ion battery cathode material prepared in Example 2 is a typical layered structure; the SEM image of the high-performance sodium ion battery cathode material prepared in Example 3 is as shown Figure 4 As shown, the high-performance sodium ion positive electrode material prepared in Example 3 also presents a layered structure, but its surface is slightly rough.
[0072] The charge and discharge curves of the sodium ion battery obtained by preparing the high performance sodium ion battery positive electrode material obtained in Examples 1 to 3 are as follows: Figure 5 As shown in Figure 2, at 2.0-4.2V and 0.2C, the discharge capacity of the sodium ion battery obtained by using the high-performance sodium ion battery positive electrode material prepared in Example 1 is 137.69mAh g -1At 2.0 - 4.2V, 0.2C, the discharge capacity of the sodium ion battery obtained by preparing the high-performance sodium ion battery cathode material in Example 2 is 150.52mAh g -1 At 2.0-4.2V and 0.2C, the discharge capacity of the sodium ion battery obtained by preparing the high-performance sodium ion battery cathode material obtained in Example 3 was 139.20mAh g -1 .
[0073] The cycle performance of the sodium ion batteries prepared in Examples 4 to 6 is shown in the figure below: Figure 6 As shown in Figure 2, at 2.0-4.2V and 1C current density, the initial capacity of the sodium ion battery prepared in Example 4 is 117.37 mAh g -1 After 100 cycles, the discharge capacity is 115.67 mAh g -1 , the capacity retention rate is 98.55%; at 2.0 - 4.2V and 1C current density, the initial capacity of the sodium ion battery prepared in Example 5 is 135.52 mAh g -1 After 100 cycles, the discharge capacity is 128.19 mAh g -1 , the capacity retention rate is 94.59%; at 2.0 - 4.2V and 1C current density, the initial capacity of the sodium ion battery prepared in Example 6 is 123.99 mAh g -1 After 100 cycles, the discharge capacity is 113.32 mAh g -1 , the capacity retention rate is 91.39%.
[0074] The XRD patterns of the sodium ion battery cathode materials prepared in Comparative Examples 1 to 3 are as follows: Figure 7 As shown, after XRD analysis, Figure 7 The diffraction peak intensity of the sodium ion battery positive electrode material prepared in Comparative Examples 1 to 3 is relatively high, indicating that it has good crystallinity and has the characteristic peak of the triclinic R3m space group, indicating that the sodium ion battery positive electrode material prepared in Comparative Examples 1 to 3 is a layered structure of the O3 phase.
[0075] The SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 1 is as follows Figure 8 As shown, the SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 2 is as follows Fig. 9 As shown, the SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 3 is as follows Fig.10 As shown, the sodium ion battery positive electrode materials prepared in Comparative Examples 1 to 3 have a typical layered structure.
[0076] The charge and discharge curves of the sodium ion batteries prepared in Comparative Examples 4 to 6 are shown in Fig.11As shown in Figure 2, at 2.0-4.2V and 0.2C, the discharge capacity of the sodium ion battery prepared in Comparative Example 4 is 145.93mAh g -1 At 2.0 - 4.2V, 0.2C, the discharge capacity of the sodium ion battery prepared in Comparative Example 5 was 146.97mAh g -1 At 2.0 - 4.2V, 0.2C, the discharge capacity of the sodium ion battery prepared in Comparative Example 6 is 130.42mAh g -1 .
[0077] The cycle performance of the sodium ion batteries prepared in Comparative Examples 4 to 6 is shown in the figure below: Fig.12 As shown in Figure 2, at 2.0-4.2V and 1C current density, the initial capacity of the sodium ion battery prepared in Comparative Example 4 is 123.38 mAh g -1 After 100 cycles, the discharge capacity is 108.81 mAh g -1 The capacity retention rate is 88.19%; at 2.0 - 4.2V and 1C current density, the initial capacity of the sodium ion battery prepared in Comparative Example 5 is 124.94 mAh g -1 After 100 cycles, the discharge capacity is 106.56 mAh g -1 The capacity retention rate of the sodium ion battery prepared in Comparative Example 5 after 100 cycles is 85.28%; at 2.0-4.2V and 1C current density, the initial capacity of the sodium ion battery prepared in Comparative Example 6 is 124.95 mAh g -1 After 100 cycles, the capacity is 107.30 mAh g -1 The sodium ion battery prepared in Comparative Example 6 has a discharge capacity retention rate of 85.87% after 100 cycles.
[0078] Figure 5 and Figure 6 The figures are respectively the charge and discharge curves and long cycle performance comparison diagrams of the sodium ion batteries obtained in Examples 4 to 6. Fig.11 and Fig.12 The figures are respectively the charge and discharge curves and long cycle performance comparison diagrams of the sodium ion batteries obtained in comparative examples 4 to 6. In the electrochemical test, the cycle stability of the sodium ion batteries obtained in Examples 4 to 6 is higher than that of the comparative example, proving that the synergistic effect of co-doping Cu, Li and Ti elements in a suitable proportion can improve the cycle stability of the nickel-manganese-based layered oxide material.
[0079] In summary, the sodium ion battery prepared from the high-performance sodium ion battery positive electrode material of Example 1 has the best long-cycle stability.
[0080] The data of 0.2 C charging capacity, 0.2 C specific discharge capacity, 1 C charging capacity, 1 C specific discharge capacity and capacity retention rate of the sodium ion batteries of Examples 4 to 6 and Comparative Examples 4 to 6 are shown in Table 4.
[0081] Table 4
[0082]
[0083] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A method for preparing a high-performance sodium ion battery positive electrode material, characterized in that: The following steps are involved: Step 1, mixing a sodium source, a nickel source, a manganese source, a copper source, a lithium source and a titanium source until uniform, to obtain a precursor powder, wherein the ratio of sodium in the sodium source, nickel in the nickel source, manganese in the manganese source, copper in the copper source, lithium in the lithium source and titanium in the titanium source is 1.05: (0.5-xyz) based on the amount of the substance: 0.5: x: 1.05y: z, where x=0.15, y=0.05, z =y; Step 2, sintering the precursor powder at 850-950° C. for 12-14 h to obtain a high-performance sodium ion battery positive electrode material; The high-performance sodium ion battery positive electrode material is a layered structure of the O3 phase. The capacity retention rate of the sodium ion battery prepared from the high-performance sodium ion battery positive electrode material at a current density of 1C is as high as 98.55%.
2. The preparation method according to claim 1, characterized in that: In step 1, the method of mixing the sodium source, nickel source, manganese source, copper source, lithium source and titanium source until they are uniform is one of dry ball milling, wet ball milling, spray drying and sol-gel method.
3. The preparation method according to claim 1, characterized in that: In step 2, the temperature is raised to 850-950°C at a rate of 4-6°C / min.
Citation Information
Patent Citations
Nickel-manganese-based positive electrode composite material, preparation method thereof and sodium ion battery
CN116936761A